STRATEGI OPTIMALISASI KESIAPAN PENDIDIK DAN PESERTA DIDIK TERHADAP PEMANFAATAN AI YANG BERTANGGUNG JAWAB DI RUANG BELAJAR: ANALISIS LITERATUR MENGENAI MITIGASI RISIKO PLAGIARISME, PENGUATAN INTEGRITAS AKADEMIK, DAN PENINGKATAN KAPASITAS LITERASI DATA - Ignatius Septo Pramesworo; Aslan, Aslan (CV. Lafadz Jaya, 2026)
This study analyses strategies for optimising the readiness of educators and learners to utilise responsible artificial intelligence (AI) in the learning environment through a literature review, focusing on mitigating the risk of plagiarism, strengthening academic integrity, and improving data literacy capacity. Findings from two main discussions show that an integrated approach—covering strict institutional policies such as AI codes of honour, authentic task design, advanced plagiarism detection technology, and data literacy frameworks such as the AILit Framework and H-AI-H model—effectively reduces plagiarism incidents by up to 40% while building students' cognitive resilience through personalised ethical learning and interdisciplinary training. This study recommends a layered national Responsible AI Use Framework for Indonesia, including mass teacher training, standardised anti-plagiarism guidelines, and a mandatory data literacy curriculum, to realise an inclusive education ecosystem in line with the Merdeka Curriculum and the 2045 golden generation vision.